Influence Cash Turnover, Receivables Turnover, Inventory Turnover, and Capital Structure on Profitability in Plantation Companies Listed on the Indonesian Stock Exchange - Gurning, Dedy (SEAN Institute, 2024)
Plantation companies in their business activities have many factors that can influence profitability. This research was conducted on Plantation Companies listed on the Indonesia Stock Exchange for the 2018-2021 period by accessing the website www.idx.co.id. The design of this research is explanatory (Explanatory Research) because this research intends to explain the influence between variables through hypothesis testing (hypothesis testing) which has been formulated, namely the influence of Cash Turnover (X1), Receivables Turnover (X2), Inventory Turnover (X3) and Structure Capital or Debt Equity Ratio (X4) to Profitability or Return on Assets (Y). The panel data approach to estimate the empirical model shows the results that the Common Effect Model is the best compared to the Fixed Effect Model and Random Effect Model. (a)The influence of the independent variable on the dependent variable partially is (1) Cash Turnover has no significant effect on the Profitability of plantation companies listed on the Indonesia Stock Exchange in 2018-2021 which is proxied by Return on Assets (ROA); (2) Receivables turnover has no significant effect on the profitability of plantation companies listed on the Indonesia Stock Exchange in 2017-2021, which is proxied by Return on Assets (ROA). (3) Inventory Turnover has a significant effect on the Profitability of plantation companies listed on the Indonesia Stock Exchange in 2018-2021 which is proxied by Return on Assets (ROA); (4) Debt Equity Ratio (DER) has a significant effect on the profitability of plantation companies listed on the Indonesia Stock Exchange in 2018-2021, which is proxied by Return on Assets (ROA). (b) The influence of the independent variable on the dependent variable simultaneously shows that Cash Turnover, Receivables Turnover, Inventory Turnover, and Debt Equity Ratio (DER) have no significant effect on the profitability of plantation companies listed on the Indonesia Stock Exchange in 2018-2021 which is proxied by Return on Assets (ROA). (c) Cash Turnover, Receivables Turnover, Inventory Turnover, and Debt Equity Ratio (DER) have met the Classic Assumption Test (Normality Test, Heteroscedasticity Test, Multicollinearity Test, and Autocorrelation Test).